Alfabetização de jovens e adultos em Barcarena nos anos 1990 - SOUZA, Maria do Carmo Soares de (2024)
The main objective of this work is to show a little, through research carried out with students and teachers, how the literacy process of young people and adults in Barcarena took place in the 1990s. to get a job in the factories, but they were prevented by lack of studies and professional qualification. Address youth and adult education, in the view of the authors Magda Soares, Literacy and Literacy 2013. Suzana Schwartz, Youth and Adult Literacy 2012. Lígia Regina Klein Literacy Who's Afraid of Teaching 2002. Luiz Antônio Marcuschi. From Speech to Writing 2010. How non-literate adults are inserted in a literate and fully written society, some tips for alphabetizing adults, what happens when an adult is literate, learns to read, write, to produce in specific situations, how educators should act so that young and adult students do not give up on their studies. Educators must skillfully encourage students to think before acting, to transform information into knowledge and knowledge into experience.